I Am Happy with My Time - Frank, Pat (Tufts Archival Research Center, 2006)
Pat Frank describes his experiences as a war correspondent with Edward R. Murrow during World War II; explains how his interactions with Germans, Japanese, and Italians give him hope that people share a fundamental humanity; and notes that the chance to watch history unfold is a great opportunity and responsibility, despite the uncertainty of the era.